PENENTUAN BIAYA PRODUKSI DENGAN METODE FULL COSTING UNTUK MENETAPKAN HARGA JUAL PRODUK CAFE BUKAN RUANG - Mahgfiroh Setiati; Rizka Ramayanti (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2023)
The purpose of this study is to determine the cost of production at the Not Ruang Cafe using the full costing method to set the price. This type of quantitative descriptive with a comparative approach. The data used are primary data and secondary data to help researchers do the calculations. The results of this study indicate that the production costs determined by the company are lower than those determined using the full costing method, because the company has not included elements of direct labor costs and factory overhead costs into production costs. The current selling price of the product only uses estimates of production costs and competitors' selling prices. In contrast to the selling price determined by the cost plus pricing method, the selling price of Anteng's milk coffee, latte and pandan latte is higher than the company's selling price. However, Long Black, Taro Latte, Matcha Latte and Chocolate products are priced below the retail price set by the company. With the cost plus pricing method, a profit of Rp 1,520,491 is obtained, which is higher than the current selling price.